Evaluation of the ambient air quality analysis of HCL, H2S and NH3 from enhanced evaporation spray system ponds on the Highveld of South Africa - ihperal@zoology.up.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Meteorology))--University of Pretoria, 2005.